GLOBECOM 2020 - 2020 IEEE Global Communications Conference 2020
DOI: 10.1109/globecom42002.2020.9322463
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Channel Profiling Using the Frequency Selectiveness of WiFi CSI Samples

Abstract: Due to the increased proliferation of WiFi in public and private spaces, there is interest in exploiting WiFi for spatial monitoring. In this paper, we aim to characterize movement or objects in a channel using Channel State Information (CSI). Channel state information represents the degree to which a wireless signal has been attenuated and delayed, and hence we hope to characterize different objects and multipath channel characteristics from CSI. We place different static objects and moving humans in a channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this way, we are able to understand how signals of different frequencies are transformed by the same channel. In the same manner that different wavelengths of light are affected uniquely by physical medium, we expect that these varying frequency subcarriers will be uniquely attenuated and delayed by channel stimuli [31]. This will offer us insight into the channel composition.…”
Section: Csi Sensing Modelmentioning
confidence: 95%
See 2 more Smart Citations
“…In this way, we are able to understand how signals of different frequencies are transformed by the same channel. In the same manner that different wavelengths of light are affected uniquely by physical medium, we expect that these varying frequency subcarriers will be uniquely attenuated and delayed by channel stimuli [31]. This will offer us insight into the channel composition.…”
Section: Csi Sensing Modelmentioning
confidence: 95%
“…Once pre-processing has been applied to CSI to accentuate human artefacts, ML is used to correlate features in CSI with corresponding changes in the channel. It has been shown that the CSI amplitude of different OFDM subcarrier frequencies can be exploited for profiling a static channel [29][30][31]. Applications that aim to profile static channels often use statistical features calculated on the CSI Amplitude profile across the domain of OFDM subcarriers [19,30].…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
See 1 more Smart Citation